Evaluation of the use of sweet potato (Ipomea batata) Agrosavia Aurora about the quality of the eggs in laying hens - Ruiz Corrales, Cristina Margarita
The present study aimed to evaluate the effect of the use of orange sweet potato (Ipomea batata) on egg quality in laying hens. For the development of this work, a complete randomized experimental design was used, in which three treatments were evaluated, T0: control treatment; T1: inclusion of 10% sweet potato flour; T2: inclusion of 10% fresh sweet potato. This experiment was carried out for 3 weeks, 180 laying hens Isa Brown race were used. With the supply of fresh sweet potato it can be seen that it influenced the weekly intake of the food in the egg weight, it is also observed that with the intake of the sweet potato flour, it influenced the height of the albumen, egg weight, size, temperature, pH, yolk color and shell thickness. The fresh sweet potato to 10% addition in the chicken diet cause positive effect in the egg weight, showing a possible improvement in the profitability of production for poultry farmers since costs are reduced in terms of balanced feed. In the case of sweet potato flour, its use also generates favorable results in egg quality; however, the dehydration and grinding process applied to obtain it makes it less feasible to incorporate it into production. According to the above, the best alternative is the supply of fresh sweet potatoes.